2006
DOI: 10.1007/s11897-006-0025-7
|View full text |Cite
|
Sign up to set email alerts
|

Screening for ventricular remodeling

Abstract: Current guidelines emphasize the importance of preventing heart failure (HF) by targeting people with preclinical forms of the disease. Accordingly, there is considerable interest in identifying left ventricular (LV) remodeling, the fundamental substrate for HF, in asymptomatic individuals in the community. Increased LV mass and asymptomatic LV systolic and LV diastolic dysfunction are the remodeling phenotypes that could be potentially considered for population-wide screening. Plasma levels of natriuretic pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 119 publications
(88 reference statements)
1
5
0
Order By: Relevance
“…Although BNP remains the most widely used biomarker to aid HF diagnosis and to stratify those at risk of developing HF, in this study multivariate analysis revealed that elevated BNP was not an independent predictor of progression. This is consistent with previous data suggesting that the performance characteristics of BNP are typically suboptimal for identifying left ventricular remodelling phenotypes unless high‐risk individuals are targeted, with other limitations, including wide biological variability and low specificity …”
Section: Discussionsupporting
confidence: 91%
“…Although BNP remains the most widely used biomarker to aid HF diagnosis and to stratify those at risk of developing HF, in this study multivariate analysis revealed that elevated BNP was not an independent predictor of progression. This is consistent with previous data suggesting that the performance characteristics of BNP are typically suboptimal for identifying left ventricular remodelling phenotypes unless high‐risk individuals are targeted, with other limitations, including wide biological variability and low specificity …”
Section: Discussionsupporting
confidence: 91%
“…However, many patients with DD are asymptomatic before the development of clinical symptoms of heart failure, 3 making accurate and cost-effective means of detection a priority. 4 Pharmacologic interventions and lifestyle modifications are critical, as worsening of diastolic function in patients with either normal or impaired diastolic function at baseline has been shown to be an independent predictor of mortality. 5 Left ventricular hypertrophy (LVH), as measured by indexed LV mass on echocardiography, is associated with impaired diastolic function, 6 especially in patients with hypertension and concentric hypertrophy.…”
mentioning
confidence: 99%
“…When performing population-based screening for asymptomatic disease, it is generally preferable to implement a sequential screening strategy, relying on a less expensive and less invasive test first, followed by a more expensive and invasive test which may have greater sensitivity and specificity (29,30). In this context, there is inevitably a net loss in sensitivity, because only a proportion of the individuals who tested positive on the first test are brought back for additional testing.…”
Section: Discussionmentioning
confidence: 99%